Les activités internationales des autochtones du Canada - Forest, Pierre-Gerlier; Rodon, Thierry (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1995)
Aboriginal peoples of Canada have never limited themselves to the national scène in their struggle to obtain the recognition of their collective rights and powers. Since 1974, this phenomenon has increased noticeably and the international activities of Aboriginal peoples can be seen as a major event in Canadian external affairs. However, Aboriginal peoples of Canada are not a homogenous group. Their participation in the international Systems or institutions is as varied as the traditions and the expectations of each aboriginal nation towards political action. Beyond a typology of the external relations of Aboriginal peoples, the approach used in this article offers new perspectives over the extent and the meaning of their international personality : without being a condition of aboriginal self-government, the participation in the international arena is certainly promoting the realization of this ideal.